Above - Bobet, Leah (Arthur A. Levine Books, 2012)
When insane exile Corner and his army of mindless, whispering shadows invade Safe, a secret, underground community of freaks and disabled outcasts, Matthew, traumatized shapeshifter Ariel, and other misfits go to the dangerous place known as Above, where Matthew makes a shocking discovery about the histories entrusted to him.